A novel LOX3-null allele (lox3-b) originated in the aromatic Basmati rice cultivars imparts storage stability to rice bran. (1st February 2022) - Bollinedi, Haritha; Singh, Neha; Gopala Krishnan, S.; Vinod, K.K.; Bhowmick, P.K.; Nagarajan, M.; Ellur, R.K.; Singh, A.K.
Highlights: Novel LOX3-null accessions were identified among Indian rice germplasm accessions. LOX3-null variants were associated with less impact on linoleic acid contents. Variation in the rancidity of LOX3-nulls was attributed to differences in the γ-oryzanol. Deletion of a C residue in exon 2 of LOX3-nulls led to non-functional LOX3 protein. A dCAPS marker based on the C deletion assist in marker assisted breeding. Abstract: Rapid deterioration of rice bran due to the LOX3 enzyme catalysed oxidation of PUFA is the major bottleneck for its utilization in various downstream applications. In the present study, we have identified a set of nine novel LOX3-null rice accessions carrying a deletion of C residue in the exon2 causing a frameshift mutation resulting in a truncated non-functional LOX3 protein. Our study, further manifested the predominance of C deletion based LOX3-null allele, named lox3-b, in the aromatic rice germplasm particularly in the Indian Basmati rice group. The LOX3-null genotypes exhibited significantly reduced rancidity, after six months of storage. They also showed significantly lower percentage reduction of linoleic acid (LA), higher γ-oryzanol content and lower hexanal content. A functional dCAPS marker designed based on the deletion polymorphism clearly differentiated LOX3 and lox3-b alleles, and has the potential application in marker assisted rice breeding programmes to develop cultivars with better bran storability.